Effect of micro-aeration and inoculum type on the biodegradation of lignocellulosic substrate. (February 2017) - Tsapekos, P.; Kougias, P.G.; Vasileiou, S.A.; Lyberatos, G.; Angelidaki, I.
Highlights: Micro-aerobic conditions were applied to enhance the methane yield of wheat straw. Oxygen load, pulse frequency and micro-aeration period were the examined variables. Extended hydrolysis and solubilization of straw were achieved due to micro-aeration. The most efficient micro-aeration strategy increased the methane yield by 7.2%. AD process was susceptible to instability at oxygen loads higher than 10 mL O2 /g VS. Abstract: The effect of various micro-aeration strategies on the anaerobic digestion (AD) of wheat straw was thoroughly examined using a mixture of inocula, containing compost and well digested sludge from biogas plant. The aim was to determine the most efficient oxygen load, pulse repetition and treatment duration, resulting in the highest methane production. The oxygen load had the largest impact on the biodegradability of straw, among the examined variables. More specifically, a micro-aeration intensity of 10 mL O2 /g VS was identified as the critical threshold above which the AD performance was more susceptible to instability. The highest enhancement in biogas production was achieved by injecting 5 mL O2 /g VS for a consecutive 3-day treatment period, presenting a 7.2% increase compared to the untreated wheat straw. Nevertheless, the results from optimisation case study indicated a higher increase of 9% by injecting 7.3 mL O2 /g VS, distributed in 2 pulses during a slightly shorter treatment period (i.e. 47 h).